Greenhouse gas emissions and production cost footprints in Australian gold mines. (10th September 2020) - Ulrich, Sam; Trench, Allan; Hagemann, Steffen
Abstract: Australia has a globally significant gold mining sector for which both greenhouse gas (GHG) emissions data and production cost data are often available on an individual mine basis. Establishing relationships between GHG emissions and production costs has the potential to shape the future of the gold industry in Australia through greater focus upon cleaner, efficient production. GHG emissions data from Australian gold mines reveal consistent, significant relationships between gold grade and GHG emissions intensity per ounce. Higher gold grades are associated with lower GHG emission intensity per ounce. Differences in both emissions intensity and gold grades exist between open pit mines, underground mines and those operations which source ore from both open pit and underground. Open pit gold mines have the highest GHG emissions intensity but lowest costs. Underground mines have the lowest GHG emissions intensity but costs that are above open pit mines. Australian gold mines exhibit declining gold grades that are predicted to continue over the coming decade. These projected lower gold grades will lead to higher GHG emissions intensities in the absence of other GHG abatement interventions. Significant opportunities exist, to materially reduce GHG emissions at Australian gold mines with interventions underway. Broader adoption of solar and wind energy, changing how underground mines are cooled and the introduction of electric vehicles and mining fleet, especially in underground mines, are key impact areas. Graphical abstract: Image 1 Highlights: Significant relationships between gold grade and GHG emissions intensity per ounce. Differences in GHG emissions intensity and production costs due to gold ore source. GHG Emissions and production cost footprints differentiated by gold ore source. Forecast declining gold grades will lead to higher GHG emissions intensities. Significant opportunities exist to reduce GHG emissions at Australian gold mines.